(untitled) (Revista de Crítica Literaria Latinoamericana, 2010)
This article tackles the study of El pez de oro (1957), by Gamaliel Churata, from a perspective that strives to take into account its heterogeneous elements. Churata’s text is eloquent in its denunciation of colonialism; yet, its complexity presents a series of challenges to interpretation. A possible route, which is explored here, goes beyond its connections with Andean religious thought, indigenismo and the avant-garde, and links El pez de oro with the Latin American Baroque cultural production.